INFLUENCE OF TECHNOGENIC POLLUTION ON BENZ(A)PYRENE СONTENT IN SILAGE - Yevstafieva, V.; Shcherbakova, N.; Kruchynenko, O.; Melnychuk, V.; Mykhailiutenko, S.; Korchan, L.; Dolhin, O.; Peredera, S. (Scientific Progress & Innovations, 2021)
The data concerning the possible ways of finding benz(a)pyrene, a harmful substance with the expressed carcinogenic and mutagenic properties, were presented in the work. The substance belongs to the first class of danger. Benz(a)pyrene is an indicator of the environmental state. As a result of migration, it gets into feeds of plant origin. According to the results of the conducted monitoring studies of feeds used for farm an-imals on private farms of Poltava region, the main source of contamination with PAH (polycyclic aromatic hydrocarbons), namely benz(a)pyrene, was determined. Its eco-toxicity was investigated. In particular, it was detected in the experimental samples of silage at a concentration of 6.72±0.22 μg/kg, fluctuating from 6.30 to7.50 μg/kg in the studied feed. To determine possible ways of contaminating silage with benz(a)pyrene, the content of this dangerous carcinogenic substance in Sudan grass and sunflower at the beginning of flowering, as well as in corn green mass was studied. The choice of plants for the experiment was based on the fact that the majority of farmers use the green mass of corn and Sudan grass, which are sown at a distance of 50–1500 m away from the Kyiv-Kharkiv highway, to put in silo pits. Comparing the level of benz(a)pyrene accumulation in the experimental samples of plants grown on lands located at a dis-tance of 500–300 m away from the highway, it was found that the super-toxin was accumulated most of all in Sudan grass (over 9.94 μg/kg). The accumulation in sunflower was somewhat less than in Sudan grass at the beginning of flowering (9.10 μg/kg, P<0.01) and in corn (8.41 μg/kg, P<0.05). During the study of average samples of the above mentioned plants, which were taken at a distance of 400–900 m and 1,000–1,500 m away from Kyiv-Kharkiv highway, the tendency of decreasing the quantitative indicator of benz(a)pyrene was registered, which correlated with the distance to the highway. Thus, at a distance of 500–900 m, the av-erage indicator in Sudan grass made 1.50 μg/kg, and at a distance of 1,000–1,500 m it decreased to0.30 μg/kg. The obtained results are of important theoretical and practical significance, as they to some extent complement the already existing scientific data on the accumulation of the carcinogen in various plants, including crops. In addition, the obtained data allow farmers to plan sowing crops taking into account the safe distance to intensive-traffic highways.